The relationship of anxiety and alcohol use disorders: a case report - Bozkurt, Oya; Pektaş, Özkan; Kalyoncu, Ö. Ayhan; Mırsal, Hasan; Beyazyürek, Mansur (Journal of Dependence, 2003)
Alcohol use disorders are usually accompanied by depression, anxiety and personality disorders. The theories that explain comorbid disorders and its etiologies in alcohol dependence propose that anxiety disorders may induce alcohol use disorder or lead it to last (self-medication) or alcohol use disorder may induce anxiety disorder or lead it to last. In addition, familial and genetic factors may either induce alcohol use disorder or anxiety disorders or lead them to last. In this article, a case which characterizes a man developing alcohol dependence to reduce his anxiety caused by panic attacks and social phobia; and to relieve “post-traumatic stres” symptoms experienced after the eartquake of August 17 was discussed within the frame of the resources in this field.
Keywords: Alcohol dependence; comorbidity; anxiety disorder; self medication